A method and application of covalent organic framework loading Anderson type heteropoly acid
By constructing a catalyst with Anderson-type heteropolyacid-loaded catalysts with covalent organic frameworks, the problem of difficulty in recycling and low desulfurization efficiency of POMs catalysts is solved, and efficient oxidative desulfurization reaction is achieved, and the catalyst has good recycling performance.
Patent Information
- Application Number
- CN202310039463.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-01-12
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-01-12
AI Technical Summary
The existing POMs catalysts are difficult to recover and reuse, and the desulfurization efficiency of catalyzed oxygen oxidation and desulfurization reaction is low under mild conditions.
By constructing a substoichiometric covalent organic framework (ECOF) of [4+3] type, the amino-modified Anderson-type MnMo6 polyacid is connected by covalent bonds to achieve stable loading and high dispersion of POMs in the ECOF nanopores to form an ECOF-POM catalyst. This catalyst is used in an aerobic oxidation and desulfurization system under mild conditions, and uses oxygen as an oxidizing agent to achieve efficient removal of thiophene sulfides.
The stable loading and high dispersion of POMs are achieved, the catalytic efficiency of oxidative desulfurization is improved (up to more than 98%), and the catalyst can be recycled again through simple treatment, solving the problem of catalyst recovery.
Smart Images

Figure CN116174036B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of an oxidative desulfurization catalyst. Background Art
[0002] The booming global economic activities have brought unprecedented energy demand, especially low-cost liquid fuels stored naturally. Sulfur compounds (thiophene and its derivatives) in liquid fuels produce sulfur dioxide during combustion, causing severe acid rain, corroding buildings and crops, changing the pH value of rivers and soil, and adversely affecting aquatic life. In recent years, countries have paid more and more attention to environmental issues, and deep desulfurization of liquid fuels has attracted widespread attention from all over the world.
[0003] Desulfurization technology can generally be divided into two categories: hydrodesulfurization and non-hydrodesulfurization. Hydrodesulfurization is an effective desulfurization technology in industry, which can remove most aliphatic and non-cyclic organic sulfides. However, high temperature (200-450℃), high pressure (3-6MPa), huge hydrogen consumption and expensive catalysts make hydrodesulfurization (HDS) urgently need to be reformed. In addition, this technology has poor desulfurization effect on DBT and its derivatives, has a negative impact on the octane number of the treated product, and leads to unnecessary hydrogenation of sulfur-free aromatic compounds. In summary, it is imperative to develop an efficient non-hydrodesulfurization deep desulfurization technology. At present, potential non-hydrodesulfurization technologies include adsorption desulfurization (ADS), extractive desulfurization (EDS), oxidative desulfurization (ODS) and biological desulfurization (BDS). Among them, ODS has the advantages of mild reaction conditions, low operating cost, high selectivity for aromatic sulfides, and can selectively convert organic sulfides into corresponding sulfoxides and sulfones compared with other desulfurization technologies. Therefore, ODS has gradually become a potential practical technology for deep desulfurization of fuel oil and has attracted widespread attention from scientists.
[0004] In the ODS process, the oxidant is one of the important factors for deep desulfurization. In the past, hydrogen peroxide or peroxy organic acid was a commonly used oxidant. Hydrogen peroxide has become the most widely used ODS oxidant due to its high oxidation activity and environmentally friendly properties. However, the use of hydrogen peroxide directly increases the cost of desulfurization. Oxygen is a more economical and environmentally friendly oxidant than peroxide, but the induction of oxygen activation requires a higher energy barrier, making it more difficult to oxidatively desulfurize fuel under mild conditions. Although the removal of sulfides such as thiophene has been achieved using oxygen as an oxidant, it requires operation under high temperature and high pressure or in the presence of a sacrificial agent. Designing a heterogeneous catalyst that can efficiently catalyze ODS using oxygen as an oxidant under mild conditions remains a very challenging topic.
[0005] Polyoxometalates (POMs, referred to as polyacids) have adjustable acidity and strong redox properties, and show excellent activity in catalyzing ODS reactions. However, the catalysts currently studied are mainly concentrated on Keggin-type POMs and POMs@MOFs, and the oxidants are mainly concentrated on hydrogen peroxide. Under mild conditions, the reaction of POMs catalyzing oxygen ODS can only be carried out in a homogeneous reaction, the catalyst is difficult to recycle, and the desulfurization efficiency also needs to be improved.
[0006] In the classical structure of polyacids, Anderson-type polyacids are polyoxymethyl esters with a single planar ring structure consisting of six edge-sharing octahedral MoO 6 A crown structure formed around a central metal oxygen octahedron. Anderson-type polyacids contain relatively more terminal oxygen, which makes the structure have high oxidation activity. The use of Anderson-type heteropolyacids as catalysts to catalyze aerobic oxidative desulfurization of diesel has been reported in the literature. However, the use of Anderson-type polyacids alone to catalyze oxidative desulfurization is limited by the high cost of homogeneous catalysis. How to select a suitable supporting material, design a recyclable POM-based heterogeneous catalyst, and use it to catalyze oxygen oxidative desulfurization reactions to improve desulfurization efficiency is an urgent problem that needs to be solved in the existing technology. Summary of the invention
[0007] The present invention aims to solve the problems that the existing POMs catalyst is difficult to recycle and reuse, and the desulfurization efficiency of the POMs-catalyzed oxygen ODS reaction is low, and provides a method and application of a covalent organic framework-loaded Anderson-type heteropoly acid.
[0008] A method for loading Anderson-type heteropolyacid on a covalent organic framework is carried out according to the following steps:
[0009] ETBC-TAPTCOF and amino-modified Anderson-type MnMo 6 The polyacid is dissolved in a mixed solution of anhydrous acetonitrile and dioxane and mixed uniformly by ultrasound, then glacial acetic acid is added as a catalyst, and mixed uniformly by ultrasound again to obtain a mixed solution, the mixed solution is stirred at room temperature, and then filtered and solids are collected, and then the solids are dissolved in acetonitrile, stirred at room temperature, filtered and solids are collected again, and finally washed to obtain ECOF-supported Anderson-type heteropolyacid;
[0010] The amino-modified Anderson-type MnMo 6 The structural formula of polyacid is [N(C 4 H 9 ) 4 ] 3 [MnMo 6 O 18 {(OCH2 ) 3 CNH 2} 2 ];
[0011] The ETBC-TAPTCOF and the amino-modified Anderson-type MnMo 6 The mass ratio of the polyacid is 1:(2-2.5); the volume ratio of the mass of the ETBC-TAPTCOF to glacial acetic acid is 1 mg:(0.0006-0.0007) mL.
[0012] The invention discloses an application of a covalent organic framework-supported Anderson-type heteropoly acid, which is applied in an aerobic oxidation desulfurization system to remove thiophene sulfides under the conditions of a surfactant, oxygen and a temperature of 85°C to 100°C.
[0013] Advantages of the present invention:
[0014] The present invention realizes functionalization while preparing ECOF by constructing a [4+3] type substoichiometric ECOF. Then, POMs are encapsulated in the nanopores of ECOF by covalent bonding with an amino-modified Anderson-type polyacid. This method realizes stable loading of POMs in the ECOF nanopores and also realizes high dispersion of POMs in the entire ECOF material. Then, the ECOF-POM catalyst is used in an aerobic oxidative desulfurization system under mild conditions. The present invention has the following advantages:
[0015] 1. Breaking the traditional rules for preparing ECOF, a substoichiometric ECOF was prepared, and then -NH 2 The functionalized polyacid and the periodic aldehyde groups in ECOF that were not involved in the condensation were connected by covalent bonds to prepare a stable heterogeneous polyacid supported catalyst, which solved the problem of using POMs alone as catalysts in homogeneous catalysis and was difficult to recycle and reuse.
[0016] 2. The ECOF-POM catalyst is used in the aerobic oxidative desulfurization system. Under the condition of amphiphilic quaternary ammonium salt as surfactant, the system can show good removal efficiency for difficult-to-degrade thiophene substances in diesel under relatively mild reaction conditions with oxygen as oxidant and no sacrificial agent. This has developed a new environmentally friendly and efficient catalytic oxidative desulfurization route.
[0017] Due to the large size of the polyacid clusters, it is difficult to form a stable connection between the solid support and the polyacid. A common method for obtaining a stable polyacid supported catalyst is to introduce functional groups on the surface of the support. The present invention achieves stable loading of POMs in the ECOF nanopores and also achieves high dispersion of POMs in the entire ECOF material. 6 The catalyst has a high catalytic efficiency for oxidative desulfurization (up to 98% or more). After the catalyst reaction, it can be recycled after simple treatment. This is the first report of ECOF-POM composite materials for oxidative desulfurization, which provides an alternative for the application of catalytic oxidative desulfurization technology and lays the foundation for the industrial application of ECOF-POM composite materials.
[0018] The invention is used for a method and application of a covalent organic framework loading Anderson type heteropoly acid. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 IR comparison diagram, a is ETBC-TAPTCOF prepared in Example 1, b is amino-modified Anderson-type MnMo prepared in Example 1 6 Polyacid, c is the ECOF-supported Anderson-type heteropolyacid prepared in Example 1;
[0020] Figure 2 PXRD comparison diagram, a is ETBC-TAPTCOF prepared in Example 1, b is amino-modified Anderson-type MnMo prepared in Example 1 6 Polyacid, c is the ECOF-supported Anderson-type heteropolyacid prepared in Example 1;
[0021] Figure 3 N 2 Adsorption comparison chart, a is ETBC-TAPTCOF prepared in Example 1, b is ECOF loaded with Anderson-type heteropoly acid prepared in Example 1;
[0022] Figure 4 XPS comparison chart, a is ETBC-TAPTCOF prepared in Example 1, b is amino-modified Anderson-type MnMo prepared in Example 1 6 Polyacid, c is the ECOF-supported Anderson-type heteropolyacid prepared in Example 1;
[0023] Figure 5 Schematic diagram of the structure of the ECOF loaded with Anderson-type heteropoly acid prepared in Example 1, a is ETBC-TAPTCOF, b is the amino-modified Anderson-type MnMo 6 More acid;
[0024] Figure 6 The curve showing the change of ODS desulfurization efficiency catalyzed by ECOF-supported Anderson-type heteropolyacid prepared in Example 1 as the reaction time increases;
[0025] Figure 7 The curve showing the change of ODS desulfurization efficiency catalyzed by ECOF-supported Anderson-type heteropoly acid prepared in Example 1 as the reaction temperature increases;
[0026] Figure 8 The curve showing the change of ODS desulfurization efficiency catalyzed by ECOF-supported Anderson-type heteropoly acid prepared in Example 1 with the increase of catalyst dosage;
[0027] Fig. 9 This is a bar graph showing the ODS desulfurization efficiency catalyzed by the ECOF-supported Anderson-type heteropoly acid prepared in Example 1 when the catalyst is reused 7 times. DETAILED DESCRIPTION
[0028] Specific implementation method 1: This implementation method is a method for loading Anderson-type heteropolyacid on a covalent organic framework, which is carried out according to the following steps:
[0029] ETBC-TAPTCOF and amino-modified Anderson-type MnMo 6 The polyacid is dissolved in a mixed solution of anhydrous acetonitrile and dioxane and mixed uniformly by ultrasound, then glacial acetic acid is added as a catalyst, and mixed uniformly by ultrasound again to obtain a mixed solution, the mixed solution is stirred at room temperature, and then filtered and solids are collected, and then the solids are dissolved in acetonitrile, stirred at room temperature, filtered and solids are collected again, and finally washed to obtain ECOF-supported Anderson-type heteropolyacid;
[0030] The amino-modified Anderson-type MnMo 6 The structural formula of polyacid is [N(C 4 H 9 ) 4 ] 3 [MnMo 6 O 18 {(OCH 2 ) 3 CNH 2} 2 ];
[0031] The ETBC-TAPTCOF and the amino-modified Anderson-type MnMo 6The mass ratio of the polyacid is 1:(2-2.5); the volume ratio of the mass of the ETBC-TAPTCOF to glacial acetic acid is 1 mg:(0.0006-0.0007) mL.
[0032] The ETBC-TAPTCOF is referred to as ECOF. The ECOF loaded with Anderson type heteropoly acid is referred to as ECOF-MnMo 6 catalyst.
[0033] The ECOF described in this embodiment is a subvalent ECOF with a [4+3] configuration prepared by a substoichiometric method using 4',4"',4""',4"""'-(1,2-ethylenediyl)tetrakis[1,1'-biphenyl]-4-carbaldehyde (ETBC) and 4,4',4"-(1,3,5-triazine-2,4,6-triyl)triphenylamine (TAPT) as raw materials, and has two free aldehyde groups in each periodic channel.
[0034] This embodiment breaks the inherent rules of traditional preparation of ECOF. Using ETBC and TAPT as raw materials, a [4+3] type substoichiometric ECOF with bex topological structure is prepared by solvothermal reaction in a solvent with a volume ratio of o-dichlorobenzene: n-butanol of 1:(0.4-0.5). Then, an amino-modified Anderson-type MnMo6 polyacid is used as a precursor to prepare a tris(hydroxymethyl)aminomethane ligand (HOCH 2 ) 3 CNH 2 Combined with Anderson type polyacid, the -NH 2 Functionalization, the grafted free amino groups can be used to connect with the periodic aldehyde groups in ECOF that do not participate in condensation through covalent bonds to obtain a covalently linked ECOF-POM composite material, achieving stable loading and uniform dispersion of polyacids in ECOF. It is then used to catalyze the desulfurization system with oxygen as the oxidant, achieving the effect of efficient oxidative desulfurization of diesel.
[0035] Advantages of this implementation:
[0036] This embodiment constructs a [4+3] type substoichiometric ECOF and realizes its functionalization while preparing the ECOF. Then, the POMs are encapsulated in the nanopores of the ECOF by covalent bonding with the amino-modified Anderson-type polyacid. This method achieves stable loading of POMs in the ECOF nanopores and also achieves high dispersion of POMs in the entire ECOF material. Then, the ECOF-POM catalyst is used in an aerobic oxidative desulfurization system under mild conditions. This embodiment has the following advantages:
[0037] 1. Breaking the traditional rules for preparing ECOF, a substoichiometric ECOF was prepared, and then -NH 2 The functionalized polyacid and the periodic aldehyde groups in ECOF that were not involved in the condensation were connected by covalent bonds to prepare a stable heterogeneous polyacid supported catalyst, which solved the problem of using POMs alone as catalysts in homogeneous catalysis and was difficult to recycle and reuse.
[0038] 2. The ECOF-POM catalyst is used in the aerobic oxidative desulfurization system. Under the condition of amphiphilic quaternary ammonium salt as surfactant, the system can show good removal efficiency for difficult-to-degrade thiophene substances in diesel under relatively mild reaction conditions with oxygen as oxidant and no sacrificial agent. This has developed a new environmentally friendly and efficient catalytic oxidative desulfurization route.
[0039] Due to the large size of the polyacid clusters, it is difficult to form a stable connection between the solid support and the polyacid. A common method to obtain a stable polyacid supported catalyst is to introduce functional groups on the surface of the support. This embodiment achieves stable loading of POMs in the ECOF nanopores and also achieves high dispersion of POMs in the entire ECOF material. 6 The catalyst has a high catalytic efficiency for oxidative desulfurization (up to 98% or more). After the catalyst reaction, it can be recycled after simple treatment. This is the first report of ECOF-POM composite materials for oxidative desulfurization, which provides an alternative for the application of catalytic oxidative desulfurization technology and lays the foundation for the industrial application of ECOF-POM composite materials.
[0040] Specific embodiment 2: This embodiment differs from specific embodiment 1 in that the volume ratio of anhydrous acetonitrile to dioxane in the mixed solution of anhydrous acetonitrile and dioxane is 1:(1.1-1.2). Other aspects are the same as specific embodiment 1.
[0041] Specific embodiment 3: The difference between this embodiment and specific embodiment 1 or 2 is that the ETBC-TAPTCOF and the amino-modified Anderson-type MnMo 6 The volume ratio of the total mass of the polyacid to the mixed solution of anhydrous acetonitrile and dioxane is 1 mg: (0.02-0.03) mL. The rest is the same as the first or second embodiment.
[0042] Specific embodiment 4: The difference between this embodiment and specific embodiments 1 to 3 is that ETBC-TAPT COF and amino-modified Anderson-type MnMo 6The polyacid is dissolved in a mixed solution of anhydrous acetonitrile and dioxane, and ultrasonically mixed for 10 min to 30 min at a power of 110 W to 130 W, then glacial acetic acid is added as a catalyst, and ultrasonically mixed again for 10 min to 30 min at a power of 110 W to 130 W to obtain a mixed solution, and the mixed solution is stirred for 24 h to 36 h at room temperature and a rotation speed of 500 rpm to 1000 rpm, and then filtered and solids are collected, and the solids are dissolved in acetonitrile, and stirred for 10 h to 16 h at room temperature and a rotation speed of 500 rpm to 1000 rpm, and then filtered and solids are collected again, and finally washed with acetonitrile and THF, respectively, to obtain ECOF-supported Anderson-type heteropolyacid. The rest is the same as the specific embodiments one to three.
[0043] Specific embodiment 5: The difference between this embodiment and specific embodiments 1 to 4 is that the ETBC-TAPTCOF is prepared according to the following steps: ETBC, TAPT and a mixed solvent of o-dichlorobenzene and n-butanol are added to a Schlenk tube, dispersed evenly by ultrasound, 10 mol / L to 12 mol / L acetic acid as a catalyst is added under shaking, dispersed evenly by ultrasound again, and then subjected to three steps of freezing-vacuuming-thawing-filling 2 Circulate to obtain a mixture, when the mixture returns to room temperature, heat the mixture at a temperature of 100°C to 120°C for 72h to 96h, after heating reaction, filter and collect the solid, first wash the solid with THF until the filtrate is colorless, then transfer to a Soxhlet extraction apparatus, wash with THF for 24h to 36h, and finally dry the solid in a vacuum drying oven at a temperature of 100°C to 120°C for more than 16h to obtain ETBC-TAPTCOF;
[0044] The molar ratio of ETBC to TAPT is 1:(1.0-1.5); the volume ratio of o-dichlorobenzene to n-butanol in the mixed solvent of o-dichlorobenzene and n-butanol is 1:(0.4-0.5); the volume ratio of the total mass of ETBC and TAPT to the mixed solvent of o-dichlorobenzene and n-butanol is 1 mg:(0.03-0.04) mL; the volume ratio of the mass of ETBC to acetic acid with a concentration of 10 mol / L-12 mol / L is 1 mg:(0.0014-0.0015) mL. The rest is the same as the first to fourth embodiments.
[0045] Specific embodiment 6: The difference between this embodiment and specific embodiments 1 to 5 is that the freezing-vacuuming-thawing-filling 2The cycle is specifically carried out in the following steps: placing the sealed Schlenk tube in liquid nitrogen, opening the piston after the solution is completely cooled, vacuuming for 2-3 minutes, closing the piston, thawing until the solvent is completely melted, opening the piston, filling with nitrogen, and closing the piston. The rest is the same as the specific embodiments 1 to 5.
[0046] Specific embodiment 7: The difference between this embodiment and the specific embodiments 1 to 6 is that the amino-modified Anderson-type MnMo 6 The polyacid is prepared according to the following steps:
[0047] ①. Put Na 2 MoO 4 ·2H 2 O is dissolved in water, a 6 mol / L to 6.5 mol / L hydrochloric acid aqueous solution is added and stirred at room temperature, and then an aqueous solution of tetrabutylammonium bromide is added and stirred, and then a solid is obtained by suction filtration, and the solid is washed with water, ethanol, acetone and ether in sequence to obtain a crude product, and the crude product is dissolved in acetonitrile, and recrystallized at a temperature of -10°C to -15°C, and suction filtered to obtain white block crystals, which are washed with acetonitrile and ether to obtain the product [N(C 4 H 9 ) 4 ] 4 [α-Mo 8 O 26 ];
[0048] The Na 2 MoO 4 ·2H 2 The mass ratio of O to the volume of water is 1g:(2.4-2.5)mL; the Na 2 MoO 4 ·2H 2 The mass ratio of O to the volume ratio of 6 mol / L to 6.5 mol / L hydrochloric acid aqueous solution is 1 g: (1.03 to 1.04) mL; the Na 2 MoO 4 ·2H 2 The mass ratio of O to tetrabutylammonium bromide in the aqueous solution of tetrabutylammonium bromide is 1:(0.6-0.7);
[0049] ②, the product [N(C 4 H 9 ) 4 ] 4 [α-Mo 8 O 26 ]、Mn(CH 3 COO 3 ·2H 2 O and (HOCH2 ) 3 CNH 2 Add to acetonitrile and reflux for 24h to 26h to obtain an orange solution. The orange solution is cooled to room temperature, and the white precipitate is removed by suction filtration. Then, the orange solution is exposed to ether vapor for 6h to 10h, and the white precipitate is removed by suction filtration again, and the filtrate is exposed to ether vapor for 2 days to 3 days. Finally, orange-red block crystals are obtained by suction filtration, which are washed with acetonitrile and ether and air-dried to obtain amino-modified Anderson-type MnMo 6 More acid;
[0050] The product [N(C 4 H 9 ) 4 ] 4 [α-Mo 8 O 26 ] and Mn(CH 3 COO 3 ·2H 2 O mass ratio is 1: (0.18-0.19); the product [N (C 4 H 9 ) 4 ] 4 [α-Mo 8 O 26 ] and (HOCH 2 ) 3 CNH 2 The mass ratio of the product [N(C 4 H 9 ) 4 ] 4 [α-Mo 8 O 26 The mass ratio of ] to the volume ratio of acetonitrile is 1 g: (17.5-18.0) mL. The rest is the same as the specific embodiments 1 to 6.
[0051] Mn(CH 3 COO 3 ·2H 2 The CAS number of O is: 19513-05-4, which is manganese acetate dihydrate.
[0052] Specific implementation method eight: This implementation method uses a covalent organic framework-supported Anderson-type heteropoly acid, which is used in an aerobic oxidation desulfurization system to remove thiophene sulfides under the conditions of surfactant, oxygen and temperature of 85°C to 100°C.
[0053] Previously, the most commonly used strategy was to use surfactants to form micelles or reverse micelles to significantly enhance the reaction rate in micellar media. The disadvantage is that the catalytic system formed is homogeneous, the catalyst is difficult to recover, and the desulfurization efficiency has room for improvement. This embodiment uses an Anderson-type polyacid as a catalyst, ECOF as a carrier, and an amphiphilic quaternary ammonium salt as a surfactant to form a heterogeneous catalytic system. The system can oxidize the difficult-to-degrade thiophene compounds in diesel into corresponding sulfone substances under relatively mild reaction conditions in the absence of a sacrificial agent, and remove them from the system by filtration. In this system, the non-polar groups of the surfactant are in contact with the non-polar organic solvent on the outside, while the polar groups are arranged inside to form a polar core, which has the ability to dissolve polar substances. Such a structure can provide a higher local reactant concentration near the catalyst, which helps to overcome the gas-solid-liquid three-phase mass transfer barrier and increase the reaction rate. On the other hand, the presence of quaternary ammonium salt can make electrons flow from the electron-rich quaternary ammonium salt to the Anderson-type polyacid, thereby converting the high-valent molybdenum ion into a very active transition state of low-valent molybdenum ion, which is further activated by oxygen into a stable +6-valent molybdenum ion. 2 It is activated into peroxy radicals, which further oxidize thiophene into sulfoxide or sulfone, thus achieving diesel oxidative desulfurization.
[0054] Specific implementation method 9: The difference between this implementation method and specific implementation method 8 is that the application method is as follows:
[0055] Add ECOF-loaded Anderson-type heteropoly acid and surfactant to the oil containing thiophene sulfide, and then heat to 85℃~100℃ at a speed of 500rpm~1000rpm. Heat for 5min~6min at a speed of 500rpm~1000rpm and a temperature of 85℃~100℃, and then introduce O 2 , in O 2 Under the conditions of atmosphere, rotation speed of 500rpm to 1000rpm and temperature of 85℃ to 100℃, the catalytic desulfurization reaction lasts for 6.5h to 11.5h;
[0056] The concentration of thiophene sulfide in the oil containing thiophene sulfide is 500ppm-1000ppm; the amount of ECOF loaded with Anderson type heteropoly acid is 0.5mg / mL-5mg / mL; the amount of surfactant is 0.0008g / mL-0.0012g / mL. Others are the same as the eighth embodiment.
[0057] Specific embodiment 10: This embodiment differs from specific embodiment 8 or 9 in that the surfactant is octadecyltrimethylammonium chloride. The rest is the same as specific embodiment 8 or 9.
[0058] The following examples are used to verify the beneficial effects of the present invention:
[0059] Embodiment 1:
[0060] A method for loading Anderson-type heteropolyacid on a covalent organic framework is carried out according to the following steps:
[0061] ETBC-TAPTCOF (30 mg) and amino-modified Anderson-type MnMo 6 The polyacid (60 mg) was dissolved in a mixed solution of 2.4 mL of anhydrous acetonitrile and dioxane, and ultrasonically mixed for 10 min at a power of 110 W, then 0.02 mL of glacial acetic acid was added as a catalyst, and ultrasonically mixed again for 10 min at a power of 110 W to obtain a mixed solution, which was stirred for 24 h at room temperature and a rotation speed of 500 rpm, and then filtered and the solid was collected, and the solid was dissolved in 100 mL of acetonitrile, and stirred for 12 h at room temperature and a rotation speed of 500 rpm, and then filtered and the solid was collected again, and finally washed with acetonitrile and THF, respectively, to obtain ECOF-supported Anderson-type heteropolyacid, which is an orange-yellow solid powder catalyst, abbreviated as ECOF-MnMo 6 catalyst;
[0062] The amino-modified Anderson-type MnMo 6 The structural formula of polyacid is [N(C 4 H 9 ) 4 ] 3 [MnMo 6 O 18 {(OCH 2 ) 3 CNH 2} 2 ];
[0063] The volume ratio of anhydrous acetonitrile to dioxane in the mixed solution of anhydrous acetonitrile and dioxane is 1:1.1.
[0064] The ETBC-TAPTCOF was prepared according to the following steps: ETBC (33.9 mg, 0.045 mmol), TAPT (21.3 mg, 0.06 mmol) and 0.2 mL of a mixed solvent of o-dichlorobenzene and n-butanol were added to a Schlenk tube, and ultrasonically dispersed for 5 min at a power of 100 W, and 0.05 mL of 12 mol / L acetic acid was added as a catalyst under shaking, and ultrasonically dispersed for 5 min again at a power of 100 W, and then subjected to three cycles of freezing-vacuuming-thawing-filling with N2 The mixture was cycled to obtain a mixture. When the mixture returned to room temperature, the mixture was heated at 120° C. for 72 h. After the heating reaction, the solid was collected by filtration. The solid was first washed with THF until the filtrate was colorless, then transferred to a Soxhlet extraction apparatus, washed with THF for 24 h, and finally dried in a vacuum drying oven at 120° C. for 20 h to finally obtain a light yellow solid powder, namely ETBC-TAPTCOF. The volume ratio of o-dichlorobenzene to n-butanol in the mixed solvent of o-dichlorobenzene and n-butanol was 7:3. The freezing-vacuuming-thawing-filling 2 The cycle is specifically carried out in the following steps: place the sealed Schlenk tube in liquid nitrogen, wait for the solution to completely cool, open the piston, evacuate for 2 min to 3 min, close the piston, thaw until the solvent is completely melted, open the piston, fill with nitrogen, and close the piston.
[0065] The amino-modified Anderson-type MnMo 6 The polyacid is prepared according to the following steps:
[0066] ①, 5gNa 2 MoO 4 ·2H 2 O was dissolved in 12 mL of water to form a transparent colorless solution, 5.17 mL of a 6 mol / L hydrochloric acid aqueous solution was added to the transparent colorless solution, and then stirred for 5 min at room temperature and a stirring speed of 500 rpm to obtain a reaction system; 3.34 g of tetrabutylammonium bromide was dissolved in 10 mL of water to obtain an aqueous solution of tetrabutylammonium bromide; the aqueous solution of tetrabutylammonium bromide was added to the reaction system, stirred for 10 min at room temperature and a stirring speed of 500 rpm, and then filtered to obtain a solid, and the solid was washed with water, ethanol, acetone and ether in sequence to obtain a crude product, and the crude product was dissolved in acetonitrile, and recrystallized at a temperature of -10°C, and filtered to obtain white block crystals, which were washed with acetonitrile and ether to obtain the product [N(C 4 H 9 ) 4 ] 4 [α-Mo 8 O 26 ];
[0067] ②, 4.00g of product [N(C 4 H 9 ) 4 ] 4 [α-Mo 8 O 26 ]、0.75gMn(CH 3 COO 3 ·2H 2O and 0.78 g (HOCH 2 ) 3 CNH 2 The mixture was added to 70 mL of acetonitrile and refluxed for 24 h to obtain an orange solution. The orange solution was cooled to room temperature, and the white precipitate was removed by suction filtration. The orange solution was then exposed to ether vapor for 6 h. The white precipitate was removed by suction filtration again, and the filtrate was exposed to ether vapor for 3 days. Finally, orange-red block crystals were obtained by suction filtration. The crystals were washed with acetonitrile and ether and air-dried to obtain amino-modified Anderson-type MnMo. 6 Polyacid, abbreviated as MnMo 6 -2NH 2 .
[0068] Figure 1 IR comparison diagram, a is ETBC-TAPTCOF prepared in Example 1, b is amino-modified Anderson-type MnMo prepared in Example 1 6 Polyacid, c is the ECOF-supported Anderson-type heteropolyacid prepared in Example 1. From the infrared comparison chart, it can be seen that 1625cm in a -1 The peaks near the wave number belong to the absorption vibration peak of -C=N- in ECOF; 2980~2850cm in b -1 The absorption peaks in the wavenumber range belong to -NH 2 Stretching vibration signal, 900~940cm -1 The characteristic absorption peak near the wave number is the Mo=O antisymmetric stretching vibration absorption peak, 660cm -1 The wave number near is the antisymmetric stretching vibration of Mo-OM. The above shows that -NH 2 Successful preparation of modified Anderson-type heteropolyacid; c is roughly between 2980 and 2850 cm -1 The wave number range belongs to polyacid-NH 2 The stretching vibration signal intensity of c is significantly reduced compared with a. -1 The stretching vibration intensity at the position of the carbonyl group was also significantly reduced, while the signal of the -C=N stretching vibration band became stronger, indicating that a covalent bond was formed between the polyacid and ECOF, indicating that ECOF-MnMo was successfully prepared. 6 .
[0069] Figure 2 PXRD comparison diagram, a is ETBC-TAPTCOF prepared in Example 1, b is amino-modified Anderson-type MnMo prepared in Example 1 6Polyacid, c is the ECOF loaded with Anderson type heteropolyacid prepared in Example 1. As can be seen from the figure, after the introduction of POMs, the position of the diffraction peak of ECOF did not change, indicating that the crystal structure of ECOF did not change. However, for ECOF, after the introduction of polyacid, ECOF-MnMo 6 The diffraction peak on the (100) crystal plane becomes weaker, indicating the occurrence of the extinction effect. In addition, the position of the characteristic diffraction peak of POM changes, further indicating that there is a certain interaction between ECOF and POM.
[0070] Figure 3 N 2 Adsorption comparison chart, a is ETBC-TAPTCOF prepared in Example 1, b is ECOF loaded with Anderson type heteropoly acid prepared in Example 1. It can be seen from the figure that compared with ECOF, after ECOF is condensed with polyacid, ECOF-MnMo 6 BET surface area and N 2 The adsorption capacity is significantly reduced, and the specific surface area is reduced from 700.9m 2 / g dropped to 118.8m 2 / g, the pore volume also dropped to 0.157m 2 / g, indicating that the polyacid occupied the nanopores of ECOF and was successfully loaded in the pores of ECOF; on the other hand, POMs have a higher molecular weight, which greatly increases the ECOF-MnMo 6 The mass density of ECOF-MnMo can further reduce the BET specific surface area. 6 The specific surface area of the catalyst is greatly reduced, but it still has a certain specific surface area and pores that are beneficial to the transport of substances during the catalytic process.
[0071] Figure 4 XPS comparison chart, a is ETBC-TAPTCOF prepared in Example 1, b is amino-modified Anderson-type MnMo prepared in Example 1 6 Polyacid, c is the ECOF-supported Anderson type heteropolyacid prepared in Example 1. As shown in the figure, in ECOF-MnMo 6 The XPS spectra of ECOF-POM show the presence of polyacids, which is similar to that of MnMo. 6 -2NH 2 Compared with ECOF-MnMo 6 The Mo3d peak in the XPS image shifts toward the high binding energy direction, indicating that MnMo 6 -2NH 2 There is an interaction between ECOF and electron transfer, which causes a change in its binding energy.
[0072] Figure 5 Schematic diagram of the structure of the ECOF loaded with Anderson-type heteropoly acid prepared in Example 1, a is ETBC-TAPTCOF, b is the amino-modified Anderson-type MnMo 6 As shown in the figure, the amino-modified Anderson-type MnMo modified by tris(hydroxymethylaminomethane) 6 The polyacid is anchored in the pores of ECOF through covalent linkage with the free aldehyde groups in the pores of ECOF, achieving uniform dispersion and stable loading of the polyacid in ECOF.
[0073] Example 1 Application of the prepared ECOF-supported Anderson-type heteropoly acid, using the ECOF-supported Anderson-type heteropoly acid as a catalyst, the application method is as follows:
[0074] ECOF-loaded Anderson-type heteropoly acid and surfactant were added to 25 mL of dibenzothiophene-containing oil, and then heated to 95 °C (80 °C, 85 °C, 90 °C, 100 °C) at a speed of 1000 rppm. At a speed of 1000 rppm and a temperature of 95 °C (80 °C, 85 °C, 90 °C, 100 °C), the mixture was heated for 5 min, and O was introduced. 2 , in O 2 Under the conditions of atmosphere, rotation speed of 1000rppm and temperature of 95°C (80°C, 85°C, 90°C, 100°C), catalytic desulfurization reaction was carried out, and the supernatant was taken regularly for HPLC analysis;
[0075] The concentration of dibenzothiophene in the dibenzothiophene-containing oil is 500 ppm, which is specifically obtained by dissolving 0.064 g of dibenzothiophene in 25 mL of decalin; the amounts of the ECOF-loaded Anderson-type heteropoly acid are 0.5 mg / mL, 1.25 mg / mL, 2 mg / mL, 3.5 mg / mL and 5 mg / mL respectively; the amount of the surfactant is 0.02 g.
[0076] The surfactant is octadecyltrimethylammonium chloride.
[0077] Figure 6 The curve of the change of ODS desulfurization efficiency catalyzed by Anderson-type heteropolyacid supported on ECOF prepared in Example 1 with the extension of reaction time. Under the same catalyst dosage (2 mg / mL) and reaction temperature (95°C), the change of desulfurization rate with reaction time was observed. As shown in the figure, it was found that with the increase of reaction time, the desulfurization efficiency also gradually increased, and the optimal time was 6.5h, and the removal rate reached 99.8%.
[0078] Figure 7The curve of the change of the desulfurization efficiency of ODS catalyzed by the ECOF-supported Anderson-type heteropolyacid prepared in Example 1 with the increase of reaction temperature. Under the same catalyst dosage (2 mg / mL) and reaction time (6.5 h), the change of desulfurization rate with the increase of reaction temperature was observed. As shown in the figure, it was found that with the increase of reaction temperature, the desulfurization rate also gradually increased. When the temperature was 95 ° C, the removal rate was the highest, reaching 99.8%. Further increasing the temperature, the removal rate did not increase but decreased, so the optimal reaction temperature was 95 ° C.
[0079] Figure 8 The curve of the change of the desulfurization efficiency of ODS catalyzed by the ECOF-supported Anderson-type heteropolyacid prepared in Example 1 with the increase of the catalyst dosage. Under the same reaction temperature (95°C) and reaction time (6.5h), the change of the desulfurization rate with the increase of the catalyst dosage was observed. As shown in the figure, it was found that the desulfurization rate gradually increased with the increase of the catalyst dosage. When the catalyst dosage was 2mg / mL, the removal rate was the highest, reaching 99.8%. Further increasing the catalyst dosage, the removal rate did not increase but decreased. This is because the excessive catalyst concentration near the catalytic reaction will indirectly reduce the reactant concentration. Therefore, the optimal reaction catalyst dosage is 2mg / mL.
[0080] Collection of products: After the reaction is completed, filter while hot, cool the filtrate to room temperature, and then place it at room temperature for 24 hours. White needle-shaped crystals will precipitate. Wash the white needle-shaped crystals with acetonitrile, and then dry them under vacuum at 50°C for 24 hours. Finally, reuse them according to the above application method.
[0081] Fig. 9 The bar graph of the ODS desulfurization efficiency of the ECOF-supported Anderson-type heteropolyacid catalyzed by Example 1 corresponding to the catalyst being reused 7 times. The reusability of the ECOF-supported Anderson-type heteropolyacid oxidative desulfurization catalyst was investigated. After each catalytic desulfurization reaction was completed, the catalyst was reused after the above-mentioned product was collected. As shown in the figure, under the same catalyst dosage (2 mg / mL), reaction temperature (95°C) and reaction time (6.5 h), ECOF-MnMo 6 After the catalyst was reused seven times, the desulfurization efficiency decreased from 99.8% at the first use to 87.6%, indicating that the catalyst has good reuse performance and has broad industrial application prospects.
Claims
1. A method for loading Anderson-type heteropolyacid on a covalent organic framework, characterized in that It is carried out in the following steps: The ETBC-TAPT COF and the amino-modified Anderson-type MnMo6 polyacid are dissolved in a mixed solution of anhydrous acetonitrile and dioxane and mixed uniformly by ultrasound, and then glacial acetic acid is added as a catalyst, and mixed uniformly by ultrasound again to obtain a mixed solution, the mixed solution is stirred at room temperature, and then the solid is filtered and collected, and then the solid is dissolved in acetonitrile, stirred at room temperature, and the solid is filtered again and collected, and finally washed to obtain the ECOF-supported Anderson-type heteropolyacid; The amino-modified Anderson-type MnMo6 polyacid has the structural formula [N(C4H9)4]3[MnMo6O 18 {(OCH2)3CNH2}2]; The mass ratio of the ETBC-TAPT COF to the amino-modified Anderson-type MnMo6 polyacid is 1:(2-2.5); the mass ratio of the ETBC-TAPT COF to the volume ratio of glacial acetic acid is 1 mg:(0.0006-0.0007) mL; The ETBC-TAPT COF is prepared according to the following steps: ETBC, TAPT, and a mixed solvent of o-dichlorobenzene and n-butanol are added to a Schlenk tube, dispersed uniformly by ultrasound, acetic acid with a concentration of 10 mol / L to 12 mol / L is added as a catalyst under shaking, dispersed uniformly by ultrasound again, and then subjected to three cycles of freezing-vacuuming-thawing-filling with N2 to obtain a mixture, and when the mixture is restored to room temperature, the mixture is heated at a temperature of 100°C to 120°C for 72h to 96h, after heating reaction, the solid is collected by filtration, the solid is first washed with THF until the filtrate is colorless, and then transferred to a Soxhlet extraction device, washed with THF for 24h to 36h, and finally the solid is dried in a vacuum drying oven at a temperature of 100°C to 120°C for more than 16h to obtain ETBC-TAPT COF; The molar ratio of ETBC to TAPT is 1:(1.0-1.5); the volume ratio of o-dichlorobenzene to n-butanol in the mixed solvent of o-dichlorobenzene and n-butanol is 1:(0.4-0.5); the volume ratio of the total mass of ETBC and TAPT to the mixed solvent of o-dichlorobenzene and n-butanol is 1 mg:(0.03-0.04) mL; the volume ratio of the mass of ETBC to acetic acid with a concentration of 10 mol / L-12 mol / L is 1 mg:(0.0014-0.0015) mL; The amino-modified Anderson-type MnMo6 polyacid is prepared according to the following steps: ①, Na2MoO4·2H2O was dissolved in water, and a hydrochloric acid aqueous solution with a concentration of 6mol / L~6.5mol / L was added and stirred at room temperature, and then an aqueous solution of tetrabutylammonium bromide was added and stirred, and then the solid was filtered out to obtain a solid, and the solid was washed with water, ethanol, acetone and ether in sequence to obtain a crude product, and the crude product was dissolved in acetonitrile, and recrystallized at a temperature of -10℃~-15℃, and filtered out to obtain white block crystals, which were washed with acetonitrile and ether to obtain the product [N(C4H9)4]4[α-Mo8O 26 ]; The mass ratio of the Na2MoO4·2H2O to the volume ratio of water is 1g:(2.4~2.5)mL; the mass ratio of the Na2MoO4·2H2O to the volume ratio of the hydrochloric acid aqueous solution with a concentration of 6mol / L~6.5mol / L is 1g:(1.03~1.04)mL; the mass ratio of the Na2MoO4·2H2O to the tetrabutylammonium bromide in the aqueous solution is 1:(0.6~0.7); ②, the product [N(C4H9)4]4[α-Mo8O 26 ], Mn(CH3COO)3·2H2O and (HOCH2)3CNH2 are added to acetonitrile and refluxed for 24h~26h to obtain an orange solution, the orange solution is cooled to room temperature, the white precipitate is removed by suction filtration, and then the orange solution is exposed to ether vapor for 6h~10h, the white precipitate is removed by suction filtration again and the filtrate is exposed to ether vapor for 2 days~3 days, and finally orange-red block crystals are obtained by suction filtration, which are washed with acetonitrile and ether and air-dried to obtain amino-modified Anderson-type MnMo6 polyacid; The product [N(C4H9)4]4[α-Mo8O 26 ] and Mn(CH3COO)3·2H2O has a mass ratio of 1:(0.18~0.19); the product [N(C4H9)4]4[α-Mo8O 26 ] and (HOCH2)3CNH2 has a mass ratio of 1:(0.19~0.2); the product [N(C4H9)4]4[α-Mo8O 26 ] and the volume ratio of acetonitrile is 1g:(17.5~18.0)mL.
2. The method for loading Anderson-type heteropolyacid on a covalent organic framework according to claim 1, characterized in that The volume ratio of anhydrous acetonitrile to dioxane in the mixed solution of anhydrous acetonitrile and dioxane is 1:(1.1-1.2).
3. The method for loading Anderson-type heteropolyacid on a covalent organic framework according to claim 1, characterized in that The volume ratio of the total mass of the ETBC-TAPT COF and the amino-modified Anderson-type MnMo6 polyacid to the mixed solution of anhydrous acetonitrile and dioxane is 1 mg: (0.02-0.03) mL.
4. The method for loading Anderson-type heteropolyacid on a covalent organic framework according to claim 1, characterized in that ETBC-TAPT COF and amino-modified Anderson-type MnMo6 polyacid were dissolved in a mixed solution of anhydrous acetonitrile and dioxane, and ultrasonically mixed for 10 min to 30 min at a power of 110 W to 130 W. Then, glacial acetic acid was added as a catalyst, and ultrasonically mixed again for 10 min to 30 min at a power of 110 W to 130 W to obtain a mixed solution. The mixed solution was stirred for 24 h to 36 h at room temperature and a rotation speed of 500 rpm to 1000 rpm, and then filtered and the solid was collected. The solid was dissolved in acetonitrile, and stirred for 10 h to 16 h at room temperature and a rotation speed of 500 rpm to 1000 rpm. Then, the solid was filtered and collected again, and finally washed with acetonitrile and THF, respectively, to obtain ECOF-loaded Anderson-type heteropolyacid.
5. The method for loading Anderson-type heteropolyacid on a covalent organic framework according to claim 1, characterized in that The freeze-vacuum-thaw-N2 filling cycle is specifically carried out in the following steps: place the sealed Schlenk tube in liquid nitrogen, open the piston after the solution is completely cooled, vacuum for 2min~3min, close the piston, thaw until the solvent is completely melted, open the piston, fill with nitrogen, and close the piston.
6. The use of a covalent organic framework loaded with Anderson type heteropoly acid prepared as claimed in claim 1, characterized in that It is used in aerobic oxidation desulfurization system to remove thiophene sulfides under the conditions of surfactant, oxygen and temperature of 85℃~100℃.
7. The use of a covalent organic framework loaded with Anderson-type heteropoly acid according to claim 6, characterized in that The application method is as follows: Add ECOF-loaded Anderson-type heteropoly acid and surfactant to the oil containing thiophene sulfides, then heat to 85°C~100°C at a speed of 500rpm~1000rpm, heat for 5min~6min at a speed of 500rpm~1000rpm and a temperature of 85°C~100°C, then introduce O2, and catalyze the desulfurization reaction for 6.5h~11.5h at an O2 atmosphere, a speed of 500rpm~1000rpm and a temperature of 85°C~100°C; The concentration of thiophene sulfide in the oil containing thiophene sulfide is 500ppm~1000ppm; the amount of ECOF loaded with Anderson type heteropoly acid is 0.5mg / mL~5mg / mL; the amount of surfactant is 0.0008g / mL~0.0012g / mL.
8. The use of a covalent organic framework loaded with Anderson-type heteropoly acid according to claim 7, characterized in that The surfactant is octadecyltrimethylammonium chloride.
Citation Information
Patent Citations
(R)-1-(2-hydroxy-1-phenethyl) thiourea modified Mn-Anderson type heteropolyacid catalyst as well as preparation method and application thereof
CN105797769A
(R)-1-(1-phenethyl)thiourea modified Al-Anderson type heteropolyacid catalyst and preparation method and application thereof
CN106622371A